Efektivitas Layanan Informasi Teknik Modeling Berbantuan Media Film Untuk Meningkatkan Pemahaman Mengembangkan Kemampuan Entrepreneur Peserta Didik: Effectiveness Of Film Assistant Media Modeling Information Services To Improve Understanding Of Developing Entrepreneur Skills Of Students - Nahdiah Nahdiah; Muhammad Andi Setiawan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The purpose of this study was to determine the effectiveness of information services with modelling techniques assisted by film media to improve understanding in developing entrepreneurial abilities of students in Palangka Raya 2 Vocational High School. The research methodology used was an experiment, and the test used was one group pretest-posttest. Sampling is determined by random sampling technique. Data collection techniques use observation, and scale of entrepreneurial understanding. The results of the Paired-Sample T Test show that knowledge of entrepreneurs has increased, the first average of 71.13 to 87.06 with the average number of increases of 16. The results of the t-test are 5.807, and the T-table has a significant level of 0, 05 which is 2,048. Ha is accepted if T is calculated ≥ T-table. T count (5.807) is greater than T-table (2.048), so Ha is received, and Ho is rejected. It means